N′-[(E)-2-Hydroxy-5-methoxybenzylidene]-2-methoxybenzohydrazide - Baharudin, M. Syukri. (International Union of Crystallography, 2012)
The molecule of the title compound, C(16)H(16)N(2)O(4), adopts an E conformation about the azomethine C=N double bond. The dihedral angle formed by the benzene rings is 18.88 (9)°. The molecular conformation is stabilized by an intramolecular O—H⋯N hydrogen bond, which forms an S(6) ring. In the crystal, the molecules are linked into chains parallel to [001] by N—H⋯O hydrogen bonds. The chains are further connected into a three-dimensional network by π–π stacking interactions with centroid–centroid distances of 3.6538 (10) and 3.8995 (11) Å.